Between Make-Believe and Make-Belief: : children and their performances in recreational play installations - Santos, Nathalia Scheuermann dos; Carvalho, Rodrigo Saballa de (Revista Brasileira de Estudos da Presença, 2022)
Based on Early Childhood Social Studies and Performanc e Studies, this article aims to analyze the ways children in Early Childhood Education, aged 3 to 5 years, produce performances during play in recreational play installations, as the result of research with children. The methodol ogy is based on the Mosaic Approach and on the proposition of recreational play installations. Through the analyses, two units were defined: a) make-believe performances; b) make-belief performances. Thus, it was possible to make inferences about the free movement of children between make-believe and make-belief performances through their body modulations, gestures and voices.